Findings from the 2014 Labor Force Survey in Sierra Leone - Margolis, David; Rosas, Nina; Turay, Abubakarr; Turay, Samuel (Washington, DC: World Bank, 2016)
The 2014 Labor Force Survey report seeks to contribute to solutions to the jobs challenge in Sierra Leone through a foundational analysis of the country’s first dedicated labor survey in nearly three decades. The report provides an overview of the employment situation in Sierra Leone, ranging from labor force participation to the types of employment among the working-age population. Through analysis of specialized modules, the report sheds light on key constraints to self-employment in agricultural activities and non-farm household enterprises, which are, respectively, the first- and second-largest sources of jobs in the economy. It also highlights the extent of informality in both wage employment and non-farm self-employment as well as how an individual’s status in the labor market relates to income poverty. The report also presents information on skills levels and how basic skills are acquired by the working age population. Finally, the report discusses issues related to youth employment and the specific constraints faced by youth in gaining access to productive job opportunities.